Radiative cooling smart glass / Nur Aqila Mohamed Fuzi and Wan Nordiana Wan Ali - Mohamed Fuzi, Nur Aqila; Wan Ali, Wan Nordiana (2023)
An innovative solution is sought to address the escalating global energy demand and the environmental impact of conventional cooling methods. In this context, the development of radiative cooling smart glass is proposed as a potential energy-efficient building technology. The limitations of traditional glass windows and existing smart glass technologies have been thoroughly investigated, emphasising the pressing need for a transformative approach. The primary objectives of this study encompass the conceptualisation of design ideas, the creation of a functional prototype, and the demonstration of radiative cooling smart glass performance. Furthermore, an analysis of its marketability potential was conducted, facilitating its widespread adoption in the construction industry. However, the study does recognise certain limitations. Data scarcity, experimental constraints, and potential technological advancements may influence the scope and implications of the research. Additionally, an in-depth economic analysis of adopting radiative cooling smart glass is not fully addressed, including initial investment costs and affordability considerations for various building types and regions.